2015
DOI: 10.1134/s0040579515010017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular turbulent evaporation in a gravitational field

Abstract: An analysis of the convective mechanism of the evaporation of a motionless liquid layer into a closed space has been carried out. It has been shown that the intensity of evaporation is comparable with the intensity of momentum transport in the laminar turbulent region of flows in smooth pipes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In experiments on the study of mixing in multicomponent systems at different pressures and compositions , and diffusion of a mixture of solution vapors into an inert gas , , convective flows were observed leading to a synergistic effect associated with a significant increase in the rate of mixing of the system components. At the same time , the predominant transfer of the component with the highest molecular weight was noted, which is not typical for diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments on the study of mixing in multicomponent systems at different pressures and compositions , and diffusion of a mixture of solution vapors into an inert gas , , convective flows were observed leading to a synergistic effect associated with a significant increase in the rate of mixing of the system components. At the same time , the predominant transfer of the component with the highest molecular weight was noted, which is not typical for diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of multicomponent mixing in gas mixtures with significant difference in diffusion coefficients have shown that, under certain conditions, convective instability may occur in them, followed by appearance of structured flows [10,11]. Further experimental [12][13][14] and computational-theoretical [15][16][17] studies have shown variety of thermophysical concentration flows at the boundary of "diffusion-convection" regime change. Feature of registered flows is that occur in gas systems under condition of decrease in the density of mixture with height, which is not typical for diffusion.…”
Section: Optical Experimental Visualization Of Convective Flows Durin...mentioning
confidence: 99%
“…A feature of experimental studies [16,17] was that concentration gravitational convection was implemented in systems with an initial stable stratification of the mixture density. Further study of the change in the "diffusion-concentration gravitational convection" regimes showed that the emergence and the development of convective regimes significantly depends on the ratios between the diffusion coefficients of the components, the pressure and the initial composition of the mixtures studied [18][19][20][21], and the geometric characteristics of the cavities and the properties of the medium [22], whose influence was analyzed in the similar problems of the heat-gravitational convection [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the results presented in [16][17][18][19][20][21][22] consists in the study of transition states caused by the multicomponent diffusion. However, it is difficult to estimate the influence of diffusion mechanisms on the convective component of the emerging near-boundary currents, since the multicomponent diffusion transfer is determined by the simultaneous action of several concentration gradients.…”
Section: Introductionmentioning
confidence: 99%